Association between cerebral small vessel disease and malnutrition risk: a retrospective cross-sectional study - Liu, Junyi; Lin, Jie; Zhuang, Jieying; Luo, Qian; Wang, Huijuan; Xiao, Ruiyan; Yang, Xudong; Cai, Jiangping (Frontiers in Neurology, 2025)
IntroductionMalnutrition is associated with increased morbidity and mortality from multiple diseases. However, the relationship between cerebral small vessel disease (CSVD) and malnutrition or malnutrition risk remains underexplored. This retrospective study investigated the association between malnutrition risk and CSVD, along with its common imaging markers.MethodsA total of 806 participants from a neurology department underwent cranial MRI scans and nutritional assessments. The presence of imaging markers of CSVD, including white matter hyperintensities, lacune, perivascular spaces, and cerebral microbleeds, was evaluated by expert neurologists. Malnutrition risk was assessed using the Geriatric Nutritional Risk Index (GNRI) and Controlling Nutritional Status (CONUT) scores. Logistic regression, subgroup, and interaction analyses were performed to evaluate the associations between malnutrition risk, CSVD, and its common imaging markers.Results and discussionAfter adjusting for potential confounders, patients at risk of malnutrition, as identified by both the GNRI and CONUT scores, exhibited more severe CSVD and its common imaging markers. Further analyses revealed interactions between GNRI score and smoking, highlighting potential modifying effects on the relationship between malnutrition risk and CSVD. Collectively, malnutrition risk, as assessed by objective nutritional indices, is independently associated with CSVD and its common imaging markers. These results emphasize the importance of addressing malnutrition in the prevention and management of CSVD.